Does Brand Love and Brand Image Have a Strong Impact on Word of Mouth? (Evidence from the Indonesian Vocational School) - Satria, H W; Hidayat, D P (KnE Social Sciences, 2018)
This research focuses on the analysis of brand love and brand image influence on word of mouth in Vocational Education Program of Universitas Indonesia (Vokasi UI). The method used is quantitative approach by analyzing the existing variables through multiple regression analysis (multivariate) by spreading questionnaires to 96 students in Vokasi UI. The results of this study illustrate the relationship between brand love and brand image to word of mouth of the brand Vokasi UI within the student, where brand love has a significant relationship to word of mouth while brand image has little significance to word of mouth. Keywords: vocational education, brand love, brand image, word of mouth (WOM)